2008
DOI: 10.1213/ane.0b013e3181804a5d
|View full text |Cite
|
Sign up to set email alerts
|

Functional Residual Capacity Changes After Different Endotracheal Suctioning Methods

Abstract: FRC is reduced in postcardiac surgery patients after suctioning, regardless of which method is used. Certain patients may have very pronounced changes of FRC. Routine FRC measurements could complement respiratory monitoring to optimize respiratory therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
3
20
0
1
Order By: Relevance
“…A study by Heinze et al 27 . (2008) analyzed changes in functional residual capacity of 20 postoperative cardiac surgery adult patients after suctioning with OSS and CSS in different ventilatory modes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Heinze et al 27 . (2008) analyzed changes in functional residual capacity of 20 postoperative cardiac surgery adult patients after suctioning with OSS and CSS in different ventilatory modes.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of endotracheal suction on lung volume may depend on the ventilatory mode and settings, the suctioning technique and duration, as well as on the ratio between the diameters of the endotracheal tube and the suction catheter 21,27 . Therefore, this study provided us with evidence of safety to continue using OSS, which is the most widely used in NICUs, since there were no statistically significant differences in oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…[51][52] Recent studies measured the impact of various suctioning methods and modes of ventilation and found that irrespective of ventilation mode, or whether open or closed suctioning was used, a significant loss of FRC occurred. [48][49][50][51] In a study by Lindgren et al, FRC as measured by EIT decreased by 58±24% of baseline after disconnection of the endotracheal tube and a further 22±10% during open suction itself. 50 It is probable that some form of recruitment manoeuvre may be necessary to attenuate the impact of LPVS, particularly after circuit disconnection and the application of suction.…”
Section: When Do You Recruit Lungs?mentioning
confidence: 94%
“…36,42 A number of studies have been conducted in adults demonstrating the significant losses associated with circuit disconnection and the application of suction to the airways. [48][49][50] One paediatric study compared open and closed suction and the impact on lung volume. 51 Choong and colleagues demonstrated using inductive plethysmography that the greatest loss of lung volume is related to disconnection from the circuit and subsequently recommended the use of closed suction units.…”
Section: When Do You Recruit Lungs?mentioning
confidence: 99%
“…대상자로부터 인공호흡 기를 분리한 후 기도를 흡인하는 개방형 방법은 폐쇄형 방법에 비 해 분비물을 더 많이 제거할 수 있는 반면 [6], 폐유순도, 일회호흡량 및 산소포화도를 감소시키는 단점이 있다 [7]. 최근 …”
unclassified